2019
DOI: 10.32604/phyton.2019.09017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particle Matters on Plant: A Review

Abstract: The particle matter, particularly the suspended particle matter (PM ≤ 2.5) in the air is not only a risk factor for human health, but also affects the survival and physiological features of plants. Plants show advantages in the adsorption of particle matter, while the factors, such as the leaf shape, leaf distribution density and leaf surface microstructure, such as grooves, folds, stomata, flocculent projections, micro-roughness, long fuzz, short pubescence, wax and secretory products, appeared to play an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Plants with larger leaf areas demonstrate more capable PM reduction than others with smaller leaf areas [38]. Furthermore, PM does not only accumulate on the leaf surface but also on the wax layer [39]. Relative humidity has also been found to be correlated with PM reduction, whereas pH affects the deposition velocity of fine particles [30].…”
Section: The Effect Of Reducing Pm Of Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants with larger leaf areas demonstrate more capable PM reduction than others with smaller leaf areas [38]. Furthermore, PM does not only accumulate on the leaf surface but also on the wax layer [39]. Relative humidity has also been found to be correlated with PM reduction, whereas pH affects the deposition velocity of fine particles [30].…”
Section: The Effect Of Reducing Pm Of Plantsmentioning
confidence: 99%
“…Notably, P. tobira had a high photosynthetic rate but showed the lowest CADR. Many studies have shown that the effective reduction in CO 2 in plants depends not only on their photosynthetic rate but also on other environmental factors [38][39][40][41][42][43][44][45][46][47]. For example, the effective reduction in CO 2 is also influenced by environmental conditions such as humidity and temperature [14].…”
Section: The Effectiveness Of Plants At Reducing Co2 and Controlling ...mentioning
confidence: 99%
“…e four kinds of trees showed little difference in terms of trapping particulate matter in the dew deposition stage, but there were significant differences in their ability to trap particles after the evaporation process (see Figure 4). e ability of plants to capture particle matter is related to multiple factors, including leaf shape and the leaf surface microstructure [36]. According to their leaf morphology, conifers have the strongest ability to trap particles in dew.…”
Section: Factors Affecting Leaf Interception Of Particlesmentioning
confidence: 99%
“…Furthermore, the concentration of PM in the atmosphere can directly influence the amount of PM accumulation on the leaf [21]. Under a high PM concentration, plants can accumulate more PM than plants grown in a lower PM concentration environment [22]. However, PM adversely affects plant life [23].…”
Section: Introductionmentioning
confidence: 99%